THE EFFICIENCY OF GUM-SILICA CMPOSITE FOR REMOVING OF WASTEWATER TURBIDITY - M. R. Majeed; Wafaa W. AL-Qaysi; F.H.Abdulla (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A novel mixed natural coagulant has been developed to remove sewage pollutants and heavy metals from Qanat- al- Jayesh by using low cost adsorbent natural materials. In these materials, significant interaction contains Arabic gum mixed with extracted silica from rice husk ash (natural coagulants) by the Batch device approach, using two variables, pH values ranging from 5-8 and contact times between 0.25-5 hrs. All wastewater samples were collected after treatment by adsorbents and examined for determination of residual heavy metal concentrations: Pb, Ni, Zn and Cu by atomic absorption spectroscopy (AAS), turbidity, pH, total dissolved salts (TDS), electrical conductivity (EC) and total salinity (TS). The results obtained indicate The coagulation process’ highest level of effectiveness was 95.2% for gum-silica composite with the weight 8 gm for reducing turbidity. In comparison, The coagulation process’s least effective efficiency was 80.6%, with the weight 4 gm of gum-silica composite. On the other pH values, Turbidity, TDS, TS, and EC were reduced in the waste water sample after being treated by gum-silica composite under standard water values. This mixture can be used to remove heavy water pollutants during treatment.